Production of Digital Climatic Maps Using Geostatistical Techniques - Hussain Zaydan Ali; Saad H. Farraj (Journal of Madenat Alelem University College, 2014)
There is an increasing demand for girded datasets of climate variables from fields such as hydrology, ecology, agriculture, climate change research and climate model verification. The girded climate data sets developed are very suitable for digital data storage and access. The temperature is the most important climatic elements. It effects on the various human activities. There is a mutual relationship between temperature and climate. It is the base motivation engine for the rest of the climate elements. Consequently this paper attempted to make spatial interpolation, of annual and monthly maximum temperature in Iraq for the period from 1970 to 2010 using spatial geostatistics tools in ArcGIS Version 9.3. This paper presents a methodology to produce accurate climatic maps. Validation of produced maps was examined by different criteria.